Evaluation of the microbubble system in the reduction of thermotolerant coliforms of water origin: Evaluación del sistema de microburbujas en la reducción de coliformes termotolerantes de origen hídrico - Basilio-Rojas, Mónica Caroline (2023)
Objective: Evaluate the effect of the microbubble system on the reduction of thermotolerant coliforms of water origin. Materials and methods: Experimental quantitative study. The population was made up of the water body located in the Ventanilla Wetlands (HV), Callao Region. The sample was non-probabilistic, the volume used was 117.5 L. Results: There were 27 water samples that passed through the microbubble system for treatment. The initial HV water sample presented a coliform concentration of 1700 NMP/100 mL. The median concentration of thermotolerant coliforms after passing through the microbubble system was 450NMP/100mL. The median concentration of coliforms in the water samples that was treated in the microbubble system for 30 minutes (200 NMP/100 mL) was lower in relation to the contact time of 15 and 45 minutes, respectively. Furthermore, the median concentration of coliforms in the water samples treated at a pressure of 40 PSI and 50 PSI was 450 NMP/100 mL, being lower than when a pressure of 60 PSI was applied. The median concentration of thermotolerant coliforms in the samples treated by the microbubble system is different in the three time groups evaluated (p-value < 0.05), reaching its lowest concentration at the contact time of 30 min. Conclusions: The microbubble system reduces the concentration of thermotolerant coliforms. The contact time in the microbubble system has a significant effect on reducing coliform concentration.